ANALYSIS OF THE FREQUENCY-DOMAIN CORRELATION TECHNIQUE FOR DETECTING IMPACT DAMAGES AND DETERMINING THE DYNAMIC RESPONSES OF RC BRIDGE PIERS - Karnakar, Y.; Kumari, M. Santhosha; Kumar, G. Sunil (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
In this work, we looked at the possibilities of frequency-domain-based correlation approaches (damage correlation indices) in the area of impact damage detection in reinforced concrete columns. For this work, researchers used a novel ultra-high drop hammer experiment technique to model the effects of medium-sized vehicles striking bridge piers by hitting four scaled-down reinforced concrete pier components. Using an acceleration acquisition device, the frequency response functions of the members were measured both before and after the damage occurred. As shown in the experiments, the damage correlation indexes (DCI) that accounted for the multi-order modal frequencies correctly identified the piers' damage levels. In addition, using the commercial software LSDYNA, an impact finite element model and a modal analysis technique were constructed, both of which were matched with the trials. Finally, the impact processes between medium-sized vehicles and reinforced concrete piers were simulated using a setup of the finite element parameters that matched the experimental data. Based on damage indices, a peak impact force (PIF) formula for vehicle impact situations was presented to ensure that structural design specifications are met.